Effect of Pasture Height on the Development of Free-Living Stages of Haemonchus contortus and Haemonchus placei - Bassetto, Cesar Cristiano [UNESP]; Santos, Michelle Cardoso [UNESP]; Magro, Natalia Mizuhira [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (MDPI, 2025)
Haemonchus contortus and Haemonchus placei infect different species of ruminants, but when small ruminants and cattle share the same pasture, cross-infections can occur. Weather conditions and the herbage microenvironment influence the development and survival of larvae during the free-living stage. Development of free-living stages (eggs, L1, L2, and L3) for both nematode species in sheep faeces deposited on short grass (4 cm) and tall grass (60 cm) ground was evaluated during nine days at the beginning of the rainy season. Rainfall occurred during five of the nine days assessed, and the tall and short grass environments demonstrated different temperatures, with a maximum of 34.0 °C to 42.0 °C and 31.0 °C to 38.0 °C and a minimum of 12.0 °C to 17.0 °C and 10.0 °C to 24.5 °C for the short and tall grass, respectively. Due to the development of eggs into infective larvae (L3), decreased egg counts were observed over time in faecal samples from both species and environments. However, some eggs were still present in samples until eight days post-deposition among tall grass. In both environments, the development times for all larval stages were similar. Small numbers of H. contortus larvae were found in the soil and grass, whereas no H. placei larvae were found. In conclusion, the trend of development in different environments was similar for both nematode species; however, the tall grass environment provided better conditions for the development of larval stages of both Haemonchus species.